The gene : an intimate history - Mukherjee, Siddhartha (New York : Scribner, 2016)
The Pulitzer Prize-winning author draws on his scientific knowledge and research to describe the magisterial history of a scientific idea, the quest to decipher the master- code of instructions that makes and defines humans; that governs our form, function, and fate; and that determines the future of our children.
Includes bibliographical references (pages 551-554) and index.
Keywords: Genetics -- History; Heredity; Genes